Approaches for Enhancing Mathematics Learning of Students with Learning Difficulties (The Educator Journal, 2022)
Mathematics, commonly taken as a complicated subject, has been further challenging for students with learning difficulties. Learning difficulties are the difficulties of learners acquiring the knowledge and skills to the average level expected of those of the same age, primarily because of mental disability or cognitive disorder. Effective teaching approaches are required to meet the needs of diverse students in enhancing mathematics learning. This paper explores the approaches for enhancing mathematics learning for students with learning difficulties. The armchair research adopts document study or library study to explore the techniques to enhance students’ mathematics learning with learning difficulties. The findings showed students’ perception of the learning of mathematics greatly affects students’ motivation to engage in learning mathematics and achievement. The positive perception of students encourages them for effective learning. Some of the approaches to enhance mathematics learning for students with learning difficulties include: giving praise at the appropriate time; developing problem-solving abilities; guiding to identify the reasons other than personal factors; finding the reasons for lacking effort in the subject, providing opportunities for students to showcase their abilities in the classroom; encouraging and supervising learning habits and analyzing the attributions of success and failure after each exam. These approaches are useful to enhance the learning of students with learning difficulties in our classroom situation, and they become helpful to the teachers.